Foot Reflexology with Caring Consciousness to Reduce Pain in Older Adults: An Integrative Review - Elisa Rosas Cervantes; María de Jesús Jiménez González; Rosalina Aparecida Partezani Rodrigues; Daiane Fernandes; Kevin Julián Aya Roa (Florence Nightingale Journal of Nursing)
AIM: To analyze the evidence available on foot reflexology with application of caring consciousness to reduce pain in older adults